Analysis of follicular events in owl monkeys (Aotus azarai infulatus) using B-mode and Doppler ultrasound - Coutinho, L. N. [UNESP]; de Brito, M. B S [UNESP]; Monteiro, F. O B; de Andrade, R. S.; da Conceição, M. E B; Feliciano, M. R. [UNESP]; de Castro, P. H G; Teixeira, P. P M [UNESP]; Vicente, W. R R [UNESP] (My University, 2013)
Ultrasound (B-mode) was used to analyze follicular events in 12 trained female owl monkeys (Aotus azarai infulatus). The animals were examined every 48 hours for over 90days to measure and map follicular growth in both ovaries and to measure (using Doppler velocimetry) local hemodynamic changes during the peri-ovulatory stage. There were 44 follicular growth events, each with two or three follicular waves, and a mean ± SEM interval between events of 17 ± 1.13 days. There were various hemodynamic changes during follicular growth; both vascular resistance index and pulsatility index decreased during the time when the follicle diameter peaked. Thus, both B-mode and Doppler ultrasound were useful for monitoring ovarian follicular events in owl monkeys. © 2013 Elsevier Inc.
Keywords: Aotus sp.; Follicular dynamics; Gynecology; Neotropical primates; Ovary; Animalia; Aotus (primate); Aotus azarai; Aotus trivirgatus; Primates